Financial management and analysis workbook : step-by-step exercises and tests to help you master financial management and analysis - 438906 Peterson, Pamela P.; Fabozzi, Frank J.; Habegger, Wendy D. (Hoboken, N.J. : John Wiley & Sons, 2004)
36